PENERAPAN AKAD IJARAH PADA PELAYANAN UMRAH PERSPEKTIF FATWA DSN-MUI - rizki, laila (Program Studi Hukum Ekonomi Syariah, 2025)
This study aims to understand how the Ijarah contract is implemented in Umrah services at PT Al Fajr Travelindo Wonosobo branch based on the DSN-MUI fatwa No. 112/DSN-MUI/IX/2017 concerning the Ijarah Contract. This research approach is qualitative based on field research. Primary data was obtained through observation and interviews with stakeholders. Data analysis was carried out using a descriptive method to describe the practice of implementing the Ijarah contract in Umrah services in the view of the DSN-MUI fatwa. The research findings reveal that the implementation of the Ijarah Contract at PT Al Fajr Travelindo Wonosobo Branch is in accordance with the DSN-MUI Fatwa both in terms of the form of the contract, pillars and conditions consisting of aspects of shighat, 'aqidain, ujrah, manfaah, and other important aspects in the Ijarah contract, namely time and the work of the ajir. However, transparency regarding additional costs needs to be explained from the outset to avoid elements of gharar (unlawful belief), which could undermine the validity of the contract.